2019
DOI: 10.1111/jfpp.14081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of egg white protein and soy protein fortification on physicochemical characteristics of banana pasta

Abstract: Research was conducted to investigate the effects of egg white protein and soy protein powder addition on physicochemical properties of banana pasta. The levels of protein fortification were 5, 10, and 15% of banana flour (w/w) for each type of protein. Pasta made from 100% of durum wheat semolina and 100% of banana were used as controls. The addition of soy or egg white protein showed significant differences on physicochemical properties compared with semolina pasta and pure banana pasta. Type of protein, lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Pasta dough was then extruded through the spaghetti die 2.25 mm diameter. Pasta was cooked in boiling water (100 • C) based on its optimum cooking time prior to analysis [17].…”
Section: Pasta Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pasta dough was then extruded through the spaghetti die 2.25 mm diameter. Pasta was cooked in boiling water (100 • C) based on its optimum cooking time prior to analysis [17].…”
Section: Pasta Preparationmentioning
confidence: 99%
“…It has also been reported that soy protein isolate addition enhanced gluten-free rice spaghetti quality [16]. Previous research has been carried out to incorporate soy protein isolate and egg white protein into banana flour and has improved the cooking quality and textural properties of banana pasta [17]. The aim of this study was to investigate the effects of the protein type (egg white protein and soy protein) and the level of protein addition on nutritional qualities (total phenolic content, antioxidant capacities and amino acid profiles) and digestibility properties (starch digestibility and protein digestibility) of gluten-free pasta based on banana flour.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been carried out to enhance lupin protein functionality (e.g., solubility, emulsification, and foaming activity) through the application of proteolytic enzymes in order to match that of soy (50). Fava is another sustainable and low-cost source of protein that is particularly rich in lysine and threonine and has high protein digestibility (42).…”
Section: Characteristics Of Grain Proteinsmentioning
confidence: 99%
“…The addition of grain proteins can increase total protein and amino acid contents in beverages (4). In infant formula, the partial substitution of whey protein with 50% grains proteins resulted in a beverage with protein digestibility similar to milk (42). However, the quality of the final product was closely associated with process parameters.…”
Section: Enriching Foods With Grain Proteins: Opportunities and Challmentioning
confidence: 99%
See 1 more Smart Citation